Validity Analysis of Science Learning Devices Integrated Learning Model Connected Type on Light Topics - Yulisara Yulisara; Prabowo Prabowo; Nadi Suprapto (IJORER : International Journal of Recent Educational Research, 2022)
This research aims to produce a suitable connected-type integrated learning model for science learning on the topic of light. The product specifications of the learning tools developed include lesson plans, worksheets, handouts, questionnaires and test instruments. The learning tools developed were reviewed by three validators. The research data were analyzed descriptively. The results showed that the results of the validation of the development of science learning tools were suitable for use in learning, with the following results: Learning Implementation Plan (i.e RPP) got a mode score of 3 (valid) and Cronbach Alpha 0,83 with the criteria of almost perfect agreement, Student Worksheets got a score of mode three (valid) and Cronbach Alpha 0,91 with the criteria of almost perfect agreement, Handout get a mode 4 score (very valid) 0.73 with the criteria of substantial agreement, the Cognitive Learning Outcome Test gets a mode 3 score (valid) and Cronbach Alpha 0,85 with the criteria of almost perfect agreement, the affective assessment sheet gets a mode 4 score (very valid) and Cronbach Alpha 0,85 with the criteria of almost perfect agreement, the psychomotor assessment sheet gets a mode 4 score (very valid) Cronbach Alpha 0,77 with the criteria of substantial agreement, and the student response questionnaire gets mode score 4 (very valid) Cronbach Alpha 1,00 with the criteria of almost perfect agreement. Based on the data analysis, it can be concluded that the learning tools developed are valid and suitable for use in learning.